PROGRAM DIVERSIFIKASI PRODUK OLAHAN IKAN PATIN BERBASIS ZERO WASTE DI KELURAHAN PAHANDUT SEBERANG - Maryani, Maryani Maryani; Ratnasari, Ida Ratnasari; Nursiah, Nursiah Nursiah (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
Abstract: Pahandut Seberang urban village is one of the centers of catfish fishery cultivation in Palangka Raya City. The main focus of fish farmers in the Pahandut Seberang area as a partner area is the development of fish farming only. Farmers' attention to the diversification of processed fish products to increase the added value of this commodity has never been thought of before. The facilitation of technology package (Ipteks) community diversification of processed fish products that applies the principle of zero waste that utilizes all parts of catfish, namely meat, skin, tail, bones and head needs to be done. The purpose of this PKM is to increase partners' knowledge and skills on diversification of processed catfish products by applying the concept of zero waste. The method used in achieving these goals is the active participatory empowerment of the community through collaboration with partners, namely the transfer of knowledge and technology through training activities for diversification of processed catfish products by applying the concept of zero waste. The results achieved from this PKM activity that is an increase in knowledge and skills of partners in an effort to increase the diversification of processed local fishery products so as to increase the added value of catfish, can also apply the concept of zero waste in the processing of catfish, so that income more optimal society. Keywords: diversification, catfish, zero waste, Pahandut Seberang.